Culbertson on Interest Structure: Comment - Wehrle, L. S. (Quarterly Journal of Economics, 1958)
Although current theory of the maturity structure of interest rates is in no sense complete or integrated, it is a far more acceptable body of doctrine than is indicated in John Culbertson's recent article.' It is true that since the theory exists only among the pages of scattered journal articles it is extremely difficult for one to form a correct perspective of its current status. Culbertson's article, while informative and interesting in its description of institutional demand for securities, does little to lessen this difficulty since it presents a description of the current theory that is both incomplete and, in places, incorrect. This note will set forth an interpretation of existing theory and will discuss Culbertson's theoretical treatment of expectations.2 Both because of its development and for expositional convenience, the theory will be discussed under two headings: expectations and uncertainty. The discussion of expectations refers to the influence on present interest rates of expected future rates while the discussion of uncertainty refers to the influence on present rates of uncertainty of future rates. The term expectations refers to a measure of central tendency and the terms uncertainty and risk both refer to measures of dispersion of an investor's subjective probability distribution of anticipated outcomes. Irving Fisher's statement concerning expectations -the present long rate is an average of expected short rates discounted over the life of the longest security assumes unanimous and certain expectations of future interest rates. The current version relating to expectations, developed by John Hicks,4 Nicholas Kaldor,5 Michal